2017
DOI: 10.1097/brs.0000000000001801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreceptors in Diseased Cervical Intervertebral Disc and Vertigo

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 47 publications
2
61
1
1
Order By: Relevance
“…Recent studies have identified possible objective measures of neck contribution in those diagnosed with cervical vertigo . When compared to healthy control subjects, Johnston et al found that a prolonged reduction in vestibular response to head movement (ie, VOR) when patients attempted to acquire visual targets with cervical soft tissue disorders and normal neuro‐otologic examinations .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have identified possible objective measures of neck contribution in those diagnosed with cervical vertigo . When compared to healthy control subjects, Johnston et al found that a prolonged reduction in vestibular response to head movement (ie, VOR) when patients attempted to acquire visual targets with cervical soft tissue disorders and normal neuro‐otologic examinations .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified possible objective measures of neck contribution in those diagnosed with cervical vertigo. 17,30,31 When compared to healthy control subjects, Johnston et al found that a prolonged reduction in vestibular response to head movement (ie, VOR) when patients attempted to acquire visual targets with cervical soft tissue disorders and normal neuro-otologic examinations. 31 Their results suggest that neck limitations, due to pain or stiffness, manifest an exaggerated proprioceptive response and subsequent disproportionate VOR suppression, which translates into subjective symptoms of dizziness and imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is only limited data about the prevalence of CV. The study by Karlberg et al (9) showed that vertigo and subjective balance disturbances are common complaints in the patients with cervical root compression (10). Another study showed that vertigo was present in 50% of patients with cervical spondylosis (10-13), while cervical spondylosis was the cause of dizziness in 65% of elderly patients in another study (6).…”
mentioning
confidence: 95%